Analysis Of Risk Factors Of Breast Cancer In Women Before Menopause In Haji Adam Malik Hospital Medan In 2020 - Imelda Idawati Siagian (Jurnal Kajian Kesehatan Masyarakat, 2020)
Breast cancer is the second leading cause of death after uterine cancer and the most common cancer in women. According to the Word Health Organization (WHO) that the incidence of breast cancer as many as 1,677,000 cases. Breast cancer is the most common cancer suffered by women. The study aims to analyze the risk factors for breast cancer in women before menopause at Haji Adam Malik General Hospital Medan in 2020. The study uses analytic studies with case control design by selecting female who diagnosed with breast cancer as a case group while those not diagnosed with breast cancer as a group control. The population is all patients who diagnosed with breast cancer. For the control population are patients who not diagnosed with breast cancer who are doing an examination in the oncology room. The sample is 45 people. with a ratio of 1: 1 ie 45 cases and 45 controls. Data analysis was performed by univariate, bivariate with chi square and multivariate analyzes with logistic regression tests at α = 0.05. The results of the study that there are influences on breast cancer risk factors based on age of menarche (0,000), parity (0.002), gestational age (0,000), history of breastfeeding (0.001), obesity (0,000) and smoking history (0,000) in women before menopause. Depend on the six dominant influences on breast cancer, is the age of first pregnancy. The conclusion conducted that the influence of menarche age, parity, age of first pregnancy, history of breastfeeding, obesity and smoking history on the occurrence of breast cancer in women before menopause. It is recommended for women before menopause to prevent breast cancer by reducing their exposure to risk factors that cause breast cancer and making early detection of breast cancer.